Matrix Metalloproteinase 9 as Biomarker for Malignant Mammary Tumors in Dogs - S Alani, Islam; S Al Biaty , Huda (The Iraqi Journal of Veterinary Medicine, 2024)
Canine mammary tumors (CMTs) are frequently occurring types of tumor in female dogs. Matrix metallopeptidase 9 (MMP-9) plays a role in dismantling the extracellular matrix during normal bodily functions and diseases, including cancer. The goal of this research was to evaluate the serum levels of MMP-9 as a potential diagnostic indicator for CMTs using the ELISA method. We collected tissue samples from mammary glands and blood specimens from 50 dogs suspected of having CMTs and 30 healthy control dogs. Histological examination was used to diagnose the mammary tumors, with findings indicating that 88% of the cases were malignant CMT and 12% were benign. According to ELISA results, there was a statistically considerable elevation in the mean serum level of MMP-9 in malignant cases (199.09 ng/ml) compared to benign cases (56.721 ng/ml) and controls (36.055 ng/ml). MMP-9 serum levels were significantly correlated with dogs aged 10–15 years, as well as with female dogs. In terms of stage and grade of the disease, the mean levels of MMP-9 increased as the disease progressed (Stage IV: 343.235 ng/ml). However, there was no correlation with the grade of the disease, and in regard to MMP-9 serum levels, it was not feasible to distinguish between newly diagnosed cases and recurring cases. In conclusion, measuring serum MMP-9 levels may aid in assessing the presence of malignancies in dogs with mammary tumors‎‎‎.